Good Corporate Governance Perspective In Islamic Banking Towards Improving Financial Performance - Imran, Ali; Faisal, Faisal; Firdaus, Anhar (International Journal of Economics (IJEC), 2025)
The implementation of Good Corporate Governance in Islamic banking institutions is intended to foster public trust, improve performance and maintain the stability of banking activities. Good Corporate Governance is a manifestation of banking governance in implementing the principles of openness, accountability, liability, independence and fairness. Implementation of good banking governance principles from a sharia perspective as a form of management responsibility to stakeholders. This research was conducted at Islamic Bank using a quantitative descriptive approach. This research uses Confirmatory Factor Analysis. This analysis is intended to provide an overview of Islamic Bank's performance. From the research results, the quality of transparency, accountability, responsibility, professionalism and fairness shows very good figures and there is an increase in performance from the previous year. This achievement is in line with the increasing commitment of Islamic Bank's top management in an effort to improve the bank's performance. Especially in an effort to improve Good Corporate Governance performance. In all lines of bank activity, this is also inseparable from the increasing demands for Islamic bank performance in terms of good governance.